The Prevalence and Severity of Gingivitis in High School Students in Gaza Strip - Palestine: : Cross-sectional Study - ElShanti, Amjad F. H.; Aldirawi, Ali; Mehjez, Ashraf; Zaida, Mohammed; Abu Nada, Ibrahim; Abu Nada, Mohammed (Jour Med Resh and Health Sci, 2020)
Background: There are limited data about the epidemiology of gingivitis in Gaza Strip, Palestine. The aim of the current study was to determine the prevalence and severity of gingivitis among high school students in Gaza strip. Methods: Cross-sectional study was conducted. A total of 408 students from both genders aged between 15-19 years old were selected from different areas of Gaza Strip by multistage sampling method (simple random for selecting the school, and stratified random sampling for student selection). Data of study were obtained through (periodontal examination kit and questionnaire). The data were collected in questionnaire filled by self-administration that consist of three sections; personal data, student general health conditions and oral hygiene practices. Before data collection, permission was obtained from the Ministry of Education. The schools were informed about the purpose of the study and its goal. The written informed consent from the student himself were obtained. Result: Average age of sample units was (16.92 + 0.78) years old. The percentage of males was 42.9%. According to the governorate distribution of the sample, 18.4% of them were from North Gaza, 38% were from Gaza City, while 15.4% were from Middle Camps, 18.3% from Khanyounes, and 9.8% from Rafah. The main findings of the current study revealed the prevalence rate of gingivitis among high school students was 97.1%. According to gingival index (GI), the average of GI was (1.5+0.80), where 28.5% of gingivitis cases were mild cases, while 44.5% of them were moderate, and 27% were of severe gingivitis. There was no significant difference in the average of gingival index according to gender (t=1.35, P=0.178), where the average of GI among males was (1.6+0.8), while that of females was (1.5+0.18). According to sociodemographic factors, there were no differences in averages of GI except for governorates (F=3.7, P=0.05), and for Paternal educational level (F=3.1,P=0.027), where the highest average of GI was that of those live in Gaza city (1.63+ 0.77), and North Gaza (1.63+ 0.82) and those whose fathers of illiteracy (1.73+ 0.95) and basic (1.66+0.78) educational levels. Moreover, there was statistically high significant direct correlation between GI and PI (R=0.63, P=0.000). Conclusion: The results of the current study revealed that GI average of high school students in North Gaza and Gaza City was the highest in Gaza Strip, and this finding need more investigation in future study to explain the reason of this significant difference in GI average according to governorates. Also, the findings of this study confirmed that the paternal educational level is considered as a risk factor for gingivitis, where the students whose fathers of low educational level have high probability to complain from gingivitis than those whose fathers of high educational level.